PENINGKATAN DISIPLIN WAKTU DENGAN BIMBINGAN KELOMPOK TEKNIK HOME ROOM KELAS XI SMA N 1 NALUMSARI - Liza Tri Lestari (STKIP PGRI SUMENEP, 2024)
Discipline is an important aspect to be considered in the realm of education, especially discipline related to time management, as punctuality influences the formation of good character in the learning process at school. This article describes the level of change in students' time discipline after the implementation of group guidance using the Home Room Technique for Grade XI students at SMA N 1 Nalumsari. This research is an action research in guidance and counseling (PTBK) with the following stages: 1. Planning, 2. Action, 3. Observation, and 4. Reflection conducted in 2 research cycles, with three meetings in each cycle. The results of this research during the pre-cycle stage. Data collection techniques involved interviews, observations, and documentation. The findings of this research prove that the students' time discipline increased by 39 points, initially scoring an average of 37 in the pre-cycle stage categorized as very poor (VP), now reaching 76 categorized as good (G). This study indicates that teachers should utilize the Home Room Technique group guidance in improving student discipline, especially punctuality in arriving at school.